Thieves of Bay Street : how banks, brokerages, and the wealthy steal billions from Canadians - Livesey, Bruce (Random House Canada, 2012)
This book sets out to reveal why Canada has become a popular place for investment fraud and thievery, and what the consequences are and not just for small investors who can lose a lifetime of savings with one wrong turn. It examines how bankers and brokers and the very wealthy rob from investors and companies. Thieves of Bay Street explores how our vaunted financial institutions peddle dangerous investment products and contributed to the U.S. subprime mortgage crisis, the reverberations of which are threatening entire national economies. It's about the ways that credit rating agencies, underwriters, analysts and lawyers enable fraud and how regulators and law enforcement sit on the sidelines and do nothing to stop the fiascos from unfolding. If, like so many of us, you've bought the line that Canada's financial industry is safe and sound and worthy of your respect, prepare to be robbed of something yourself, your faith.